The Effect of Leaf Traits on the Excitation, Transmission, and Perception of Vibrational Mating Signals in the Tea Leafhopper Empoasca onukii Matsuda (Hemiptera: Cicadellidae) - Yao Shan; Qiuyi Yao; Qisheng Jia; Jiping Lu; Xiaoming Cai; Zongmao Chen; Lei Bian (Plants)
The physical properties of plants affect the transmission of plant-borne vibrational signals, which many herbivorous insects use for communication. Male calling signals (MCaSs, with sections S0, S1, and S2) and courtship signals (MCoSs, with sections S1 and S2) of Empoasca onukii Matsuda (Hemiptera: Cicadellidae), a major pest of tea plant, have a multicomponent structure. The same MCaS was repeatedly played back on different leaves of a tea branch, and parameters of the transmitted signal and female responses were measured on the leaf inhabited by females. We also measured the signal parameters and behaviors of E. onukii on single leaves of different ages. The intensity of MCaSs from other leaves attenuated after they propagated to leaves on which females were located, which decreased the duration of MCaS-S2. Higher leaf thickness, leaf hardness, and leaf area were associated with an increased pulse repetition time (PRT) of MCaSs, number of pulses in MCaS-S2, and duration of MCaS-S2, respectively. MCoS-S1 had a higher dominant frequency (Df) in leaves with a long main vein and high hardness, and the PRT of MCoS-S2 was longer on thicker leaves. In the initial stage of courtship, the signal excitation of males was affected by leaf traits, especially the temporal parameters of MCaS-S2, which was the most significantly affected section after host transmission; it also had an important effect on the response delay of females. In the location stage, the signal excitation of males was not only affected by leaf traits but also interacted with the signal excitation of females. These results facilitate exploration of the interaction between leafhoppers and host plants during courtship communication and have implications for the breeding of E. onukii-resistant varieties.